Reflexión crítica sobre el impacto psicoemocional en atletas de alto rendimiento generado por la pandemia del COVID-19 - Dorino, L. (Revista Ciencias de la Educación, 2020)
The fundamental purpose of this essay is focused on reflecting on the psycho-emotional impact generated by the COVID-19 pandemic in highperformance athletes. In that sense, anxiety, stress and concerns not only due to the impact on the sports field; but also at an economic level, among other factors have been generated by the confinement situation generated by the coronavirus, making life difficult, even more so for athletes, who find it difficult to adapt their athletic training to these new living conditions, affecting their comprehensive health, including mental, because they come from the habit of an active routine of constant training, to close down and move away from the world of sports to be at home, which affects them, not only as ordinary people but as athletes of high performance. From that perspective, it was necessary to take a retrospective view regarding the pandemics that have arisen in the world and thus establish a conceptualization of COVID-19 based on the provisions of the World Health Organization, as well as the measures to combat said pandemic. Finally, to come to the reflection on the psycho-emotional impact specifically in high performance athletes.